O movimento negro e a Secretaria Especial de Políticas de Promoção da Igualdade Racial: um estudo sobre a luta por sentidos sobre a igualdade racial no Brasil - Gomes, Marcus Vinícius Peinado (2009)
We want to discuss the relationship between the Black Movement and the Brazilian State over the struggle for the meaning of racial inequality. This research aims at understanding this during the creation of the Special Secretariat of Policies to Promote Racial Equality (SEPPIR). Is the establishment of a Secretariat, with status of Department of State, capable of promoting changes in the vision of racial inequality institutionalized in Brazil? Our study aims at understanding how the conflict over the meaning of racial inequality is embodied on the Public Policy. We use the analytical category Social Movement for understanding the Black Movement, identifying some frames that guide its action. We show that these frames are related in the constitution of the place (understood as a series of links, in which the meanings of social relationships are built, where there are disputes of power on these meanings) of SEPPIR. The Black Movement‘s action put the meaning institutionalized in conflict; the State response is to use the cooptation to demobilize the movement. When discussing the relationship between Movement and the State, we identify some frames related to the naturalization of racial inequality. This institutionalized version defines our past of slavery as the main cause of inequality, not pointing to the role of racism in the maintenance of inequality. We suggest therefore that the notion of justice, repositioned by the recognition and the discussion of human rights, may be a way not only to combat this naturalization, but also to go beyond the cooptation.